2020
DOI: 10.1016/j.jmst.2019.09.017
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the high tensile strength and ductility of additively manufactured 316L stainless steel: Multiscale investigation

Abstract: We report that 316L austenitic stainless steel fabricated by direct laser deposition (DLD), an additive manufacturing (AM) process, have a higher yield strength than that of conventional 316L while keeping high ductility. More interestingly, no clear anisotropy in tensile properties was observed between the building and the scanning direction of the 3D printed steel. Metallographic examination of the as-built parts shows a heterogeneous solidification cellular microstructure. Transmission electron microscopy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 52 publications
(66 reference statements)
5
52
0
5
Order By: Relevance
“…The differences may be ascribed to the combination of fine cell structure, high density of dislocations, nano-inclusions, and residual stresses due to the SLM process. Former research [ 18 , 38 , 39 ] reported that the pre-existing dislocation networks induced by the SLM process provide substantially enhanced strength and ductility at the same time. The observation demonstrates the fact that by controlling the size of cell structures and chemical composition in conjunction with inducing dense dislocation networks and nano-inclusions, the SLM process can be utilized to reach the desired mechanical properties through optimizing the processing parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The differences may be ascribed to the combination of fine cell structure, high density of dislocations, nano-inclusions, and residual stresses due to the SLM process. Former research [ 18 , 38 , 39 ] reported that the pre-existing dislocation networks induced by the SLM process provide substantially enhanced strength and ductility at the same time. The observation demonstrates the fact that by controlling the size of cell structures and chemical composition in conjunction with inducing dense dislocation networks and nano-inclusions, the SLM process can be utilized to reach the desired mechanical properties through optimizing the processing parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Oxide-dispersion strengthened steel was also manufactured by laser metal deposition, and its density was more than 99%. Compared with unreinforced steel, its hightemperature compression strength has also been enhanced [94,95] .…”
Section: Additive Manufacturing Methodsmentioning
confidence: 99%
“…However, none of the existing studies on precipitates in LMD 316LSS conclusively report the presence of non-oxides. In a very recent study, Barkia et al 28 reported the presence of an Mo-Cr-rich zone and an Mn–Mo–Cr-rich zone (around an Mn–Si–O precipitate) within the walls of an intragranular cellular solidification structure in their LMD 316LSS. However, these cell walls are known to be sites of preferential segregation of Mo and Cr 1 , and the reported presence of Mo–Cr and Mn–Mo–Cr zones can be considered only as circumstantial evidence of the presence of non-oxide precipitates.…”
Section: Introductionmentioning
confidence: 99%